Valuation of the Multifunctional Economic Value of Rice Fields: Direct Benefits from Maize Production, Indirect Benefits from Oxygen Provision, and the Value of Preserving Rural Culture: Valuasi Nilai Ekonomi Multifungsi Lahan Sawah: Manfaat Langsung Produksi Jagung, Manfaat Tidak Langsung Penyedia Oksigen, Nilai Pilihan Pelestarian Budaya Pedesaan - Markus Patiung; Hamdi Sarimaryoni; Ernawati (Jurnal Ilmiah Sosio Agribis, 2026)
Rice paddies provide valuable ecosystem services beyond food production, yet these benefits are often excluded from agricultural economic calculations, leading to market failures and accelerating land-use conversion. This study conducted an integrated economic valuation of 110 hectares of rice fields planted with maize in Dukun Sub-district, Gresik Regency, East Java, using the Total Economic Value (TEV) framework, which includes direct use, indirect use, and option values. Direct use value, calculated using the market price method, reached Rp7,084,000,000 year⁻¹ from 1,980,000 kg of maize production. Indirect use value from oxygen services, estimated through biomass stoichiometric analysis and replacement cost method, yielded 14,868,562.5 kg O₂ year⁻¹ valued at Rp148,685,625,000 year⁻¹. Cultural preservation value, measured using the Contingent Valuation Method (CVM) with 160 respondents, showed an average willingness to pay (WTP) of Rp350,000 person⁻¹ year⁻¹ and willingness to accept (WTA) of Rp1,500,000 person⁻¹ month⁻¹, resulting in Rp296,000,000 year⁻¹. The total TEV amounted to Rp156,065,625,000 year⁻¹, with ecosystem services contributing 95.46% of the total value. These findings support the design of ecosystem services payment schemes, integration into national environmental economic accounting, and contribution to Indonesia's SDG 2, SDG 13, and SDG 15 targets.